Aetiological Risk Factors for Congenital Haemangiomas in Children - Toktosunova, Saltanat; Toktosunov, Aitmamat; Imanalieva, Aliza; Buhov, Maksim; Ibraimova, Arisel (International Journal of Child Health and Nutrition, 2026)
Background: Congenital haemangiomas are rare vascular tumours in children, and their complex aetiology involving genetic, hormonal, and environmental factors remains insufficiently understood. Purpose: This study aims to systematise and analyse data on the aetiological risk factors for congenital haemangiomas in children. The main objective was to identify key trends and patterns related to the aetiology of the disease. Methods: A structured review of 46 published sources (2013-2025) was conducted, including peer-reviewed articles, clinical case reports, and molecular studies. 91% of the included sources were published within the last 5-6 years. Materials were examined using thematic analysis, comparative methods, and systematic organisation, integrating both quantitative and qualitative approaches to assess genetic, hormonal, environmental, and perinatal risk determinants. Findings: Genetic mutations, such as missense mosaic mutations in GNAQ and GNA11, as well as the pathogenic somatic variant PIK3CA (p.His1047Gln) with an allele frequency of 8.3%, play a key role in the pathogenesis of congenital haemangiomas. Mutations in the VEGF-A and TIE2 genes also contribute to their development. Newborns with large placental chorioangiomas are more likely to develop haemangiomas. Oestrogens stimulate the proliferation of vascular cells; approximately 60% of children with periorbital haemangiomas are girls, which indicates the role of female sex hormones in the pathogenesis of haemangiomas, and hypoxia affects the expression of angiogenic inducer 61. Klippel-Trénaunay syndrome can cause haemangiomas, especially when internal organs are affected. Data showed that infantile haemangiomas occur in 75% of children with a gestational age of less than 33 weeks and in 57% of children with a gestational age of 33 to 37 weeks. Hyperemesis gravidarum can cause deficiencies of essential micronutrients in the mother, increasing the risk of congenital haemangioma by 1.75 times. The use of medications during pregnancy also increases the risk of developing a congenital hemangioma by 1.8 times Conclusion: The results of the study can be used to develop new approaches to the diagnosis and treatment of congenital hemangiomas in children, as well as to create more accurate and personalised treatment methods that account for genetic and environmental risk factors.